Respuesta :

Answer:

x = 14

Angle 1 = 6°

Angle 2 = 84°

Step-by-step explanation:

from the sign it's a right angle, so 90°

  • Find x

90 = x - 8 + 6x

90 + 8 = 7x

98 = 7x

x = 98 : 7

x = 14

------------------

check

90 = 14 - 8 + 6 * 14       (remember pemdas)

90 = 14 - 8 + 84

90 = 90

the answer is good

Find angle 1

x - 8

14 - 8 =

Find angle 2

6x

6 * 14 = 84°

--------------------

check

84 + 6 = 90°

the answer is good

Answer:

[tex]\textsf{a)} \quad \textsf{Equation}: \quad \boxed{x-8+6x=90}[/tex]

[tex]\begin{aligned}\textsf{b)} \quad m \angle 1 & =\boxed{6^{\circ}}\\ m \angle 2 & =\boxed{84^{\circ}}\end{aligned}[/tex]

Step-by-step explanation:

Part (a)

From inspection of the given diagram, the sum of the two angles is 90° (indicated by the right angle sign):

[tex]\implies m \angle 1+m \angle 2=90^{\circ}[/tex]

[tex]\implies (x - 8)^{\circ} + (6x)^{\circ} = 90^{\circ}[/tex]

[tex]\implies x-8+6x=90[/tex]

[tex]\textsf{Equation}: \quad \boxed{x-8+6x=90}[/tex]

Part (b)

To find the measure of each angle, solve the equation for x:

[tex]\implies x-8+6x=90[/tex]

[tex]\implies x+6x-8=90[/tex]

[tex]\implies 7x-8=90[/tex]

[tex]\implies 7x-8+8=90+8[/tex]

[tex]\implies 7x=98[/tex]

[tex]\implies \dfrac{7x}{7}=\dfrac{98}{7}[/tex]

[tex]\implies x=14[/tex]

Substitute the found value of x into the expression for each angle:

[tex]\implies m \angle 1=(x-8)^{\circ}[/tex]

[tex]\implies m \angle 1=(14-8)^{\circ}[/tex]

[tex]\implies m \angle 1=\boxed{6^{\circ}}[/tex]

[tex]\implies m \angle 2=(6x)^{\circ}[/tex]

[tex]\implies m \angle 2=(6 \cdot 14)^{\circ}[/tex]

[tex]\implies m \angle 2=\boxed{84^{\circ}}[/tex]